Comparative analysis of machine learning algorithms for multi-syndrome classification of neurodegenerative syndromes - Lampe, Leonie; Niehaus, Sebastian; Huppertz, Hans-Juergen; Merola, Alberto; Reinelt, Janis; Mueller, Karsten; Anderl-Straub, Sarah; Fassbender, Klaus; Fliessbach, Klaus; Jahn, Holger; Kornhuber, Johannes; Lauer, Martin; et al. (Alzheimer's Research and Therapy, 2022)
Importance The entry of artificial intelligence into medicine is pending. Several methods have been used for the predictions of structured neuroimaging data, yet nobody compared them in this context. Objective Multi-class prediction is key for building computational aid systems for differential diagnosis. We compared support vector machine, random forest, gradient boosting, and deep feed-forward neural networks for the classification of different neurodegenerative syndromes based on structural magnetic resonance imaging. Design, setting, and participants Atlas-based volumetry was performed on multi-centric T1-weighted MRI data from 940 subjects, i.e., 124 healthy controls and 816 patients with ten different neurodegenerative diseases, leading to a multi-diagnostic multi-class classification task with eleven different classes. Interventions N.A. Main outcomes and measures Cohen's kappa, accuracy, and F1-score to assess model performance. Results Overall, the neural network produced both the best performance measures and the most robust results. The smaller classes however were better classified by either the ensemble learning methods or the support vector machine, while performance measures for small classes were comparatively low, as expected. Diseases with regionally specific and pronounced atrophy patterns were generally better classified than diseases with widespread and rather weak atrophy. Conclusions and relevance Our study furthermore underlines the necessity of larger data sets but also calls for a careful consideration of different machine learning methods that can handle the type of data and the classification task best.
CRIS-Team WoS Importer:2022-05-13